Optical absorbance of RGB LEDs in pH measurement of colorimetric solution with phenol red reagent - Mohd Rumaizan Maidan Dali; Aiman Shahmi Azam; Mohamad Faizal Abd Rahman; Khairul Azman Ahmad; Nor Azlan Othman; Mohd Hanapiah Abdullah; Ahmad Fairuz Omar (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The use of red, green, and blue ( RGB ) light-emitting-diode ( LED ) is a new trend in monochromatic colorimetric sensing due to cost-effective implementation. However, the application of RGB LED in pH measurement depends on the performance of the LED colour towards the colorimetric solution of interest, hence, needs to be evaluated. This work evaluated the performance of RGB LED for pH measurement system based on colorimetric approach using phenol red as a reagent. The main objective was to identify the LED colour with the best performance in terms of signal response and a bsorbance behavior. In this work, LED and photodiode were used as optical components and NI USB DAQ with LabView as the processing software. Four samples with known pH values were prepared and tested to obtain the voltage and absorbance behavior of each LED colour. Among all, the blue LED with wavelength ranged between 450 - 495 nm showed the best sensing behavior based on its linearity and error. Both voltage response and absorbance produced linear correlation with R 2=0.883 and R 2=0.9803, respectively. The significant finding from this study is useful in selecting the best RGB LED that is suitable for colorimetric pH measurement with phenol red as its colorimetric reagent.